Research on the on-demand scheduling algorithm of intelligent routing load based on SDN. Issue 1 (21st March 2021) - Ma, Zheng; Ma, Yan; Huang, Xiaohong; Zhang, Manjun; Su, Bo; Zhao, Liang
Aiming at the traditional on-demand scheduling method of routing load, there are many problems, such as long time to complete the total task and high energy consumption. An on-demand scheduling method of routing load based on multiple SINKs is proposed. The total routing load task is sent from multiple SINK nodes to SDN network. After receiving the sub-tasks sent by SINK, the intra-cluster nodes begin to collect network data together. After the cluster heads fuse the network data transmitted by the nodes, the results are sent to SINK nodes. As a result, the shortest total task completion time is obtained, and the shortest total task completion time is used as the objective function of routing load scheduling on demand. Ant colony algorithm is used to solve the problem and complete the scheduling. Experimental results show that the proposed method has shorter completion time and lower energy consumption of total task.